Cardiorehabilitation clinical efficacy depending on the duration of the rehabilitation program and the patient’s adherence - D. M. Aronov; M. G. Bubnova (Рациональная фармакотерапия в кардиологии)
The results of studies investigating the clinical effects of cardiac rehabilitation (CR) in patients after acute myocardial infarction (MI) and cardiovascular surgery are discussed. It is known that CR programs vary in duration and dose (number of training sessions) across different countries. Systematic analysis of studies evaluating the clinical effectiveness of the program depending on its duration is relevant. The results of studies aimed at determining the minimum number of training sessions that can lead to a reliable increase in physical performance are also described. The analysis of studies on patients’ adherence to rehabilitation programs and its impact on the final clinical effects of CR is presented. It is shown that the most noticeable result is observed when patients participate in 80% or more of the required training sessions. Patients’ high adherence to physical training (PT) depends on many reasons. In this review we describe groups of patients with low adherence to PT. One of the important conditions for maintaining adherence to CR is a high-quality approach in management of such patients, giving a clearly noticeable favorable clinical effect. At the present stage, there is a need for individualization of CR strategy and transition to new forms of CR (home rehabilitation, tele-rehabilitation, etc.). When applying different "new models" of CR, it is important to maintain their high clinical efficacy.